A review of researches on internet finance. (2015) - Cao, Shuyan; Chang, Liang; Yu, Yuanyuan; Yang, Xuan
The internet and finance are accelerating into integration in the 21st century. Internet finance was firstly proposed by Ma Weihua, the former president of China Merchants Bank in July 2012. On the basis of 146 latest research literatures selected from CSSCI journals, Chinese core journals, authoritative magazines and related newspapers, this paper summarised the current research progress and trend about internet finance in China according to three dimensions, such as the sources of journals, research subjects and research contents. Then this paper summarised the researches about internet finance in the Western world. The research shows that the current researches about internet finance are not only shallow and superficial, but also lack the theoretical analyses and model applications; and the wealth-based and bank-based internet finance will be the research focus in the future.